Biopesticides Manual: Guidelines for Selecting, Sourcing and Using Biocontrol Agents for Key Pests of Tobacco 2018
DOI: 10.1079/9781789242027.0001
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the biopesticides manual.

Abstract: This manual aims to make information resources and technical advice available in order to support the deployment of biopesticides, which include microbials (e.g. bacteria, algae, protozoa, viruses and fungi), macrobials (e.g. predatory insects, parasitoids and beneficial nematodes), botanicals, and semiochemicals. It is intended to be a one-stop shop to address the information needs of the key groups who are responsible for selecting, sourcing and using biopesticides in the tobacco production system. These gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Inherently distinguished from conventional pesticides, biopesticides comprise three major categories [ 79 , 80 ]: Biochemical pest control agents or biochemical pesticides (e.g., botanical pesticides, essential oils, pheromones, hormones, natural plant growth regulators, enzymes, minerals, etc. ); Microbial pest control agents or microbiological pesticides (e.g., microorganisms); Macrobiological pest control agents or macrobiological pesticides (e.g., beneficial insects, parasitoids and entomopathogenic nematodes).…”
Section: Biopesticides: Alternatives To Synthetic Pesticides and Thei...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inherently distinguished from conventional pesticides, biopesticides comprise three major categories [ 79 , 80 ]: Biochemical pest control agents or biochemical pesticides (e.g., botanical pesticides, essential oils, pheromones, hormones, natural plant growth regulators, enzymes, minerals, etc. ); Microbial pest control agents or microbiological pesticides (e.g., microorganisms); Macrobiological pest control agents or macrobiological pesticides (e.g., beneficial insects, parasitoids and entomopathogenic nematodes).…”
Section: Biopesticides: Alternatives To Synthetic Pesticides and Thei...mentioning
confidence: 99%
“…Inherently distinguished from conventional pesticides, biopesticides comprise three major categories [79,80]:…”
Section: Biopesticide Potential Applicability and Classificationmentioning
confidence: 99%
“…These are derived from microorganisms and their metabolites (Chandler et al, 2011). Studies have reported over 3000 bacteria, 1000 viruses, 800 fungi, 1000 protozoa and 67 nematode species, all entomopathogenic to crop pests (Arjjumend & Koutouki, 2018;Holmes et al, 2019;Kutawa et al, 2016;Ruiu, 2018). These microbial biopesticides offer an alternative to synthetic insecticides with high specificity plus ecological safety (Kansiime et al, 2017).…”
Section: A) Microbial Biopesticidesmentioning
confidence: 99%
“…They can be volatile or non-volatile signals that operate long or short-range to modify the recipient's behaviour (Singh, 2014). They usually induce behavioural changes as attractants, repellants or mating disruptors (Holmes et al, 2019). Semiochemicals provide alternative solutions to synthetic pest control products.…”
Section: C) Semiochemicalsmentioning
confidence: 99%
See 1 more Smart Citation